EVALUASI PENGELOLAAN PERJANJIAN LAYANAN SISTEM INFORMASI AKADEMIK POLTEKKES KEMENKES RI PADANG MENGGUNAKAN KERANGKA KERJA COBIT 5 TAHUN 2017 - Alsri Windra Doni; Elda Yusefni . (Jurnal Sehat Mandiri, 2018)
The purpose of this study was to determine the level of capability and proposed recommendations for improvement of academic information systems polytechnic MoH RI Padang particularly manage service agreements (process APO09) using the COBIT framework 5. This research is a qualitative descriptive study using the COBIT framework 5. The procedure of this study begins by observation, interviews, literature review, gave questionnaires to the parties involved in the management of academic information systems. The survey results revealed that the level of capability for academic information system Poltkekkes MoH Padang to APO domain on APO09reached level 1 with category Largely Achieved (60.00%). The results of processing this data to base recommendations for improving the management of academic information system Poltkekkes MoH Padang to reach the target level 3. Keywords: Academic Information Systems; COBIT 5; Level Capability